Improved melt strength and processability of impact copolymer polypropylene by introducing long‐chain branching via reactive extrusion with "ene" functionalized dendrimer. Issue 6 (5th April 2022) - Jaisingh, Aanchal; Goel, Vishal; Kapur, Gurpreet Singh; Nebhani, Leena
Abstract: A generation two dendrimer (G2) having eight terminal double bonds has been prepared via esterification reaction from a dendritic precursor having eight hydroxyl end groups (G1). The reactive extrusion of impact co‐polymer polypropylene (ICP) with G1 resulted in improved processability while leading to enhanced melt strength in the case of linear low‐density polyethylene (LLDPE). G2 being an extension of G1, was melt grafted on ICP using a radical initiator to introduce long‐chain branching in the polymer backbone. The prepared samples were analyzed for their molecular weight distribution, thermal, rheological properties, and mechanical properties. Thermogravimetric analysis (TGA) and differential scanning calorimetric (DSC) analysis showed higher thermal stability and slightly higher crystallization temperature with grafting of G2 on ICP. The rheological analysis through melt flow index measurements and parallel plate rheometer indicated higher processability, melt strength, complex viscosity, and zero‐shear viscosity for ICP grafted with an optimized amount of G2. The presence of long‐chain branching was confirmed with an increase in activation energy for ICP modified with G2 as compared to neat ICP. Modified ICP samples retained their bulk mechanical properties as neat ICP. Abstract : Radical initiator assisted melt‐grafting of dendrimer having eight terminal unsaturated bonds on impact co‐polymer polypropylene backbone.